2009
DOI: 10.1097/mrr.0b013e328306351d
|View full text |Cite
|
Sign up to set email alerts
|

Long-term sick leavers with difficulty in resuming work: comparisons between psychiatric–somatic comorbidity and monodiagnosis

Abstract: The number of patients with difficulty in resuming work after long-term sick leave has increased in several European countries including Sweden. The general aim of this study was a comprehensive description--based on multidisciplinary diagnostics and assessments--of patients with the common feature of marked difficulty in resuming working life after a long absence. A particular aim was to elucidate the possible effect of comorbidity on pain descriptors, disability, quality of life, assessed working ability and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
38
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 12 publications
4
38
0
Order By: Relevance
“…The influence of psychological functioning might be underestimated in clients in vocational rehabilitation without psychiatric diagnosis. These assumption is also supported by the fact that none of the clients in our study population reported psychiatric conditions as primary health condition, but more than 75 % of the clients in our sample reported at least one comorbidity and indicated to experience periods of being depressed or anxious concerning their future -a finding that is consistent with the literature [55].…”
Section: Validitysupporting
confidence: 88%
“…The influence of psychological functioning might be underestimated in clients in vocational rehabilitation without psychiatric diagnosis. These assumption is also supported by the fact that none of the clients in our study population reported psychiatric conditions as primary health condition, but more than 75 % of the clients in our sample reported at least one comorbidity and indicated to experience periods of being depressed or anxious concerning their future -a finding that is consistent with the literature [55].…”
Section: Validitysupporting
confidence: 88%
“…Should such occupation be included in the occupational therapy context? Another example is individuals with depression, who often lose interest in daily occupations (26,27) at the same time as occupational therapy is recommended for this target group (28). These are additional areas which should be further discussed and studied.…”
Section: Discussionmentioning
confidence: 95%
“…The increase in long-term sick leave is mainly caused by an increase in mental health problems, which, often accompanied with chronic pain (Linder et al, 2009), are now among the most common reason for long-term sickness absence (Søgaard and Bech, 2009;Henderson et al, 2011). The increase in mental ill health is of societal interest as it has been proposed as a threat to the welfare of the state (Sundquist et al, 2007).…”
Section: Introductionmentioning
confidence: 99%